2020
DOI: 10.1001/jamainternmed.2020.4191
|View full text |Cite
|
Sign up to set email alerts
|

Observational Study Design Challenges—The Case of Fluoroquinolones and Aortic Disease

Abstract: 9.US Food and Drug Administration. FDA warns about increased risk of ruptures or tears in the aorta blood vessel with fluoroquinolone antibiotics in certain patients. Updated December 21, 2018. Accessed February 10, 2020. https://www.fda.gov/ drugs/drug-safety-and-availability/fda-warnsabout-increased-risk-ruptures-or-tears-aortablood-vessel-fluoroquinolone-antibiotics 10. Shah PK. Inflammation, metalloproteinases, and increased proteolysis: an emerging pathophysiological paradigm in aortic aneurysm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 4 publications
1
6
0
Order By: Relevance
“…Baseline characteristics were well balanced after PS matching between treatment groups. Our results reflect the importance of selecting appropriate comparison groups when examining safety issues of antibiotics in real‐world settings 13 . Our results also provide further safety information for individual fluoroquinolones in different follow‐up windows.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Baseline characteristics were well balanced after PS matching between treatment groups. Our results reflect the importance of selecting appropriate comparison groups when examining safety issues of antibiotics in real‐world settings 13 . Our results also provide further safety information for individual fluoroquinolones in different follow‐up windows.…”
Section: Discussionsupporting
confidence: 59%
“…Several epidemiological studies suggested that use of fluoroquinolones may precipitate potentially fatal aortic aneurysm or aortic dissection (AA/AD) events, possibly through a collagen degradation pathway 6–10 . However, whether the harmful effect observed is in line with biological mechanisms or due to methodological flaws (e.g., confounding by infection and surveillance bias) remains debated 11–13 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Consistently, without aortic disease history, short-term ciprofloxacin prophylaxis after prostate biopsy did not increase the overall risk of aortic aneurysm or rupture, however, a significantly increased risk of aortic aneurysm was noted in patients with high-risk prostate cancer most likely due to detection bias by more frequent imaging in these patients [ 186 , 187 ]. These studies raised critical concerns about confounding or surveillance bias in previous studies, and consequently, whether FQ triggers de novo aortopathy remains unclear, leaving the uncertainty to physicians for prescribing FQ to patients [ 188 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies ( 12 17 ) using large administrative datasets found that recent FQs exposure was strongly associated with an increased risk of AAD, but after adjusting for the comparator antibiotics, two recent studies ( 18 , 19 ) did not support this finding. Although a consensus on whether FQ causes de novo aortic disease has not yet been reached ( 20 , 21 ), this potential association has raised several other important clinical questions, particularly regarding whether FQs can precipitate aortic complications in patients with existing aortic disease. It has been shown that FQ exposure could increase the risk of acute aortic dissection or rupture for patients with underlying aortopathy ( 10 , 11 , 22 ).…”
Section: Introductionmentioning
confidence: 99%